2004
DOI: 10.1111/j.1601-5223.1999.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Genetics of Nordic Carnivores: Lessons from Zoos

Abstract: This paper summarizes results from genetic studies of Nordic carnivore populations bred in captivity. The conservation genetic implications of those results for the management of wild populations of the same species are discussed. Inbreeding depression has been documented in the brown bear (Ursus arctos), wolf (Canis lupus), and lynx (Lynx lynx) populations held in Nordic zoos. The characters negatively affected by inbreeding include litter size (brown bear and wolf), longevity (lynx and wolf), female reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…In captivity, a cheetah's prime reproductive period is between 3 and 10 years of age (Marker, 2000(Marker, , 2006a(Marker, , 2006b), but in general cheetah fecundity in captivity is lower than in the wild (Nowell and Jackson, 1996; also compare Marker (2000Marker ( , 2006aMarker ( , 2006b) with Kelly and Durant (2000). This is in agreement with other captive carnivorous animals (Laike, 1999;Clubb and Mason, 2007). Because we do not have data to estimate the effect of senescence on the fecundity of wild cheetahs, we consider two different cases.…”
Section: Estimating Fecunditysupporting
confidence: 72%
“…In captivity, a cheetah's prime reproductive period is between 3 and 10 years of age (Marker, 2000(Marker, , 2006a(Marker, , 2006b), but in general cheetah fecundity in captivity is lower than in the wild (Nowell and Jackson, 1996; also compare Marker (2000Marker ( , 2006aMarker ( , 2006b) with Kelly and Durant (2000). This is in agreement with other captive carnivorous animals (Laike, 1999;Clubb and Mason, 2007). Because we do not have data to estimate the effect of senescence on the fecundity of wild cheetahs, we consider two different cases.…”
Section: Estimating Fecunditysupporting
confidence: 72%
“…Grey wolf populations seem to be vulnerable to harmful effects of inbreeding. Inbreeding depression has been documented in wolves held in captivity (Pulliainen 1965;Laikre 1999). Negative effects of inbreeding have been documented also in natural populations of wolf.…”
Section: Conservation Implicationsmentioning
confidence: 97%
“…Numerous studies have now demonstrated that inbreeding reduces adult life span of a variety of animals, including mice (Miller et al 2002), carnivores (Laikre and Ryman 1991;Laikre 1999), butterflies (Saccheri et al 1998;van Oosterhout et al 2000), hymenopterans (Henter 2003;Luna and Hawkins 2004), and Drosophila. However, many studies have failed to detect inbreeding depression on adult life span ( Johnson and Hutchinson 1993;De Clercq et al 1998;Nieminen et al 2001;Markert et al 2004;Prezotti et al 2004;Radwan et al 2004;Goncalves and Di Mare 2005) and others have shown that the effect of inbreeding on adult life span varies among lines or populations (Fowler and Whitlock 1999;Swindell and Bouzat 2006) and among rearing conditions (Pray et al 1994).…”
mentioning
confidence: 99%